1969
DOI: 10.52206/jsmc.2015.5.1.644-647
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hypertension in Adult Population of Hayatabad Peshawar

Abstract: BACKGROUND: Hypertension is one of the common non communicable disease and is reported to beprevalent in 20% to 50% of the adult population, hypertension is one of the major contributor ofmortality and morbidity in developing and developed countries. The cross-sectional descriptive studywas formulated to find the prevalence and to assess different etiological factors of hypertension.MATERIAL & METHODS: This cross-sectional study among 400 adults of age 25-75 years wasconducted in months of June to December… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Moreover, 18.19% of the participants were found to be hypertensive which is comparable to other studies done on the adult population of Hayatabad Peshawar KPK. 9 High prevalence of PHTN (i.e., 56.07%) was observed in medical students of Northern Border University in Arar city, Saudi Arabia. 10 Similar results were found in another study conducted in Saudi Arabia which concluded that the prevalence of PHTN in males and females was 66.1% and 48%, respectively.…”
Section: Discussionmentioning
confidence: 93%
“…Moreover, 18.19% of the participants were found to be hypertensive which is comparable to other studies done on the adult population of Hayatabad Peshawar KPK. 9 High prevalence of PHTN (i.e., 56.07%) was observed in medical students of Northern Border University in Arar city, Saudi Arabia. 10 Similar results were found in another study conducted in Saudi Arabia which concluded that the prevalence of PHTN in males and females was 66.1% and 48%, respectively.…”
Section: Discussionmentioning
confidence: 93%